Sustainability Analysis of the Vertical Composter as an Innovative Approach for Organic Waste Management and Space-Efficient Urban Food - Sholehah, Hijriati; Nurhidayah, Nurhidayah; Rahmawati, Khairul Pahmi (Jurnal Pijar Mipa, 2025)
The waste problem is a never-ending problem, so it is everyone's responsibility to find solutions to the existing waste problem. According to data from the Ministry of Environment and Forestry in 2022, waste in Indonesia is predominantly composed of organic waste, accounting for 41.27% of the total waste. The purpose of this study was to determine plant growth by utilizing used barrels as a vertical composter for organic waste, which is useful for providing small-land farming, and to determine the quality of liquid and solid fertilizers. The method used was a laboratory experiment. The results of the study were as follows: the number of mustard green leaves was 15 cm, and the bok choy leaves were 13 cm. The total height of the mustard greens was 40 cm, and the bok choy was 20 cm. The length and area of ​​the leaves continue to increase by around 0.2 cm or more per day. The highest nutrient content in both compost and liquid fertilizer is P2O5 in Gegelengan Village, 4.223% in compost, and 5.4% in Kediri Village in liquid fertiliser, while the lowest is the N-Total content of 0.5% (compost) and 1.2% (liquid fertilizer). The research results obtained from the initial soil, solid organic fertilizer and liquid organic fertilizer met the quality standards based on the Decree of the Minister of Agriculture No. 261/KPTS/SR.320/M/04/2019.